Single-phase single stage string inverter for a grid connected photovoltaic system with integrated perturb and observe - fuzzy logic control MPPT technique / Siti Zaliha Mohammad Noor - Mohammad Noor, Siti Zaliha (2018)
This thesis presents a design of Single-phase Single stage String Inverter for Grid Connected Photovoltaic (PV) system. The proposed system use Integrated Perturb and Observe (P&O) - Fuzzy Logic Control (FLC) as a Maximum Power Point Tracking (MPPT) technique. Previous works on single-phase single stage inverter comes with various types of circuit configuration and switching techniques incorporating with MPPT. However, each topology has their advantages and disadvantages and also has their own circuit limitation. Therefore, the proposed single stage converter is designed to reduce number of power switching components with higher power conversion efficiency. The new control scheme of MPPT and Pulse Width Modulation (PWM) control technique implemented on one power circuit (single stage) without boosted DC-link is introduced. The prototype inverter is tested mainly with 340Wp PV capacity system using two series of STP170s-24/Ac PV modules. The Maximum Power Point Tracking (MPPT) is achieved by changing the modulation index and the phase angle of the inverter's output voltage. This new intelligent controlling based MPPT algorithm is implemented by combining advantages of Perturb and Observe (P&O) and Fuzzy Logic Control (FLC). The inverter switching frequency is set at 25kHz and IGBTs are used as power switching devices with full-bridge configuration. The simulation model is developed and analysed using Matlab/Simulink and Mathcad software. The simulation and experimental results are evaluated under steady state and dynamic operation. The performance of the developed string inverter is also evaluated with standard features as required by international standard. In summary, the proposed inverter complies with IEC 61727 for low THD which is less than 5% at rated output and has fast Maximum Power Point (MPP) tracking which is less than Is. In addition, the inverter has fast turn-off response during loss of utility which is less than 2s. These finding show new control technique is capable to perform effectively on PV system without DC to DC converter or any complex design of new inverter topology.